Decolonial visual resistance as a public health strategy in post-María Puerto Rico. Issue 1 (1st May 2020) - Varas-Díaz, Nelson; Padilla, Mark; Rodríguez Madera, Sheilla; Grove, Kevin; Contreras Ramírez, Violeta; Rodríguez, Sergio Rivera; Vargas-Molina, Ricardo L.; Marzán, Melissa
In this article, we explore the use of the image as a strategy to understand how natural disasters and coloniality impact the health of marginalized communities. We focus on the aftermath of Hurricane María in Puerto Rico and aim to describe how local people used the image as a strategy to challenge the invisibility fostered by coloniality and advocate for a more humane, equitable and effective public health response. We implemented a mixed methods research design including: (1) ethnographic observations, (2) qualitative in-depth interviews with 67 representatives of the health care system, (3) photographs they had taken as part of their experiences during and after the hurricane and (4) images from local newspapers and social media. In light of the findings we argue that Puerto Ricans engaged in decolonial visual resistance to manage the aftermath of the hurricane. Thus, while surviving the natural disaster, they challenged the traditional use of the image in public health endeavours.